Santri Day as a Momentum for Strengthening Character Education Values in the School Environment: Case Study MTs Ma'arif NU Sragi - Hidayat, Reza; Al Fatah, Syahma; Hidayah, Siti Nur; Kholidiyah, Novie Aulia (Institut Agama Islam Persis Bandung, 2024)
Becoming a nation with strong character is an essential goal, particularly for the Indonesian people who have endured the dark legacy of colonialism. This study aims to examine the role of Santri Day as a medium for character education and its influence in reinforcing moral and social values among Santri and the broader community. Employing a library research method combined with content analysis, the study gathers data from books, journals, newspapers, seminar proceedings, and other relevant sources. The findings highlight that Santri Day serves as a strategic moment to instill and strengthen character values in students. This is realized through various Santri Day activities, such as opening ceremonies, competitions, and collective prayer sessions, all of which contribute meaningfully to the cultivation of national character and religious identity.